2019
DOI: 10.3389/fphar.2019.00449
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA OIP5-AS1 Promotes the Proliferation of Hemangioma Vascular Endothelial Cells via Regulating miR-195-5p/NOB1 Axis

Abstract: Background: Hemangioma, which is a benign vascular neoplasm, has been demonstrated to be the most common tumor of infancy, resulting from aberrant proliferation of endothelial cells and pericytes. Objective: The aim of this study was to determine the role of lncRNA OIP5-AS1 on the proliferation and metastasis of human hemangioma endothelial cells (HemECs). Methods: In this study, we examined the expression of OIP5-AS1 and miR-195-5p in hemangiomas pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
5
26
0
Order By: Relevance
“…3 Besides, the association between OIP5-AS1 and vascular endothelial cells proliferation was also found in hemangioma, which is a benign vascular neoplasm. 17 Mechanically, we conrmed OIP5-AS1 functioned as a molecular sponge of miR-152 to regulate PAPPA expression in hVMSCs, as depicted by luciferase reporter assay, RIP and western blotting. Here, expression of miR-152 was detected to be inhibited by ox-LDL and its overexpression by transfection resulted in diminishing cell viability, migration rate and levels of PCNA and MMP-2/9 in ox-LDL-treated hVMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Besides, the association between OIP5-AS1 and vascular endothelial cells proliferation was also found in hemangioma, which is a benign vascular neoplasm. 17 Mechanically, we conrmed OIP5-AS1 functioned as a molecular sponge of miR-152 to regulate PAPPA expression in hVMSCs, as depicted by luciferase reporter assay, RIP and western blotting. Here, expression of miR-152 was detected to be inhibited by ox-LDL and its overexpression by transfection resulted in diminishing cell viability, migration rate and levels of PCNA and MMP-2/9 in ox-LDL-treated hVMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Very recently, OIP5-AS1 has been annotated to be higher expressed in human umbilical vein endothelial cells, and the association between OIP5-AS1 and vascular endothelial cells functions has also been addressed. 17,18 Nevertheless, the expression and role of OIP5-AS1 in VMSCs remain to be disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…Li and colleague's study revealed that OIP5-AS1 could promote the progression of oral squamous cell carcinoma by regulating the miR-338-3p/NRP1 axis [41]. Another study has also indicated an aggressive role of ceRNA to drive migration, invasion, and proliferation of human hemangioma endothelial cells via regulating the miR-195-5p/NOB1 axis [45]. In the present study, it was observed that OIP5-AS1 displayed low-expression, which could compete with miRNAs (hsa-miR-17-5p, hsa-miR-20b-5p, hsa-miR-761, hsa-miR-3619-5p, hsa-miR-24-3p, hsa-miR-27a, hsa-miR-338-3p, and hsa-miR-129-5p) to regulate target gene expression.…”
Section: Discussionmentioning
confidence: 98%
“…Thus far, among these hub lncRNAs, DNAJC27-AS1, AF121898, and SNX29P2 have not been reported in any study. OIP5-AS1 is an antisense lncRNA that has been reported to play a critical role in various disorders, including oral squamous cell carcinoma [40], gastric cancer [41], cardiovascular disease [42], and multiple sclerosis [43]. Li and colleague's study revealed that OIP5-AS1 could promote the progression of oral squamous cell carcinoma by regulating the miR-338-3p/NRP1 axis [40].…”
Section: Discussionmentioning
confidence: 99%